Peningkatan Aktivitas dan Hasil Belajar IPA Materi Tubuh Sehat melalui Metode Pembelajaran Jigsaw (Penelitian Tindakan Kelas Peserta Didik Kelas I Semester 1 SDN Ngiyono Tahun Pelajaran 2016/2017) - Mashadi, Mashadi (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2018)
Abstract. The purpose of this study was to improve the activities andlearning outcomes of science in class 1 students in the first semester on theHealthy Body material in Ngiyono Public Elementary School through theJigsaw learning method in the 2016/2017 school year. This type of researchis Classroom Action Research conducted in 2 cycles consisting of 2meetings with 4 stages each cycle, namely planning, implementing actions,observing, and reflecting. The research subjects were class I students,totaling 18 students. Data collection methods used are observation, tests,and documentation. The results of this study are an increase in the activitiesand learning outcomes of science students in class I. This is shown from thepre cycle average value of activities and student learning outcomes is 70.55by 7 students. In the first cycle the average value of activities and learningoutcomes of students is 78.80 by 11 students while in the second cycle theaverage value of the results of activities and student learning outcomes is86.67 by 16 students from 18 students. The activities and learning outcomesof students in science subjects in Healthy Body material in class I insemester 1 increased with the application of the Jigsaw learning method andhad fulfilled the indicator of success of 75%.